Reservation wage of female volunteer community health workers in Dhaka urban slums: a bidding game approach - Alam, Khurshid; Tasneem, Sakiba; Huq, Molla (© 2014 Health Economics Review, 2016)
This article was published in the Health Economics Review [© 2014, Alam et al.; licensee Springer.] and the definite version is available at : http://dx.doi.org/10.1186/s13561-014-0016-4 The Journal's website is at: http://healtheconomicsreview.springeropen.com/articles/10.1186/s13561-014-0016-4